"Cough Hemicrania" – An Overlapping Form of Headache: Case Reports. Issue 5 (14th April 2017) - Pavão Martins, Isabel; Viana, Pedro
Abstract : Objective: To describe two patients with recurring unilateral brief headaches that fulfilled criteria for both primary cough headache (CH) and chronic paroxysmal hemicrania (CPH). Background: CH is typically a bilateral headache, specifically triggered by cough, straining, or other Valsalva maneuvers. The report of cases sharing features with other primary headache disorders, such as CPH, suggest common pathogenic mechanisms. Methods: Case reports. Results: Two patients (one man), aged 55 and 64, had a two‐year history of daily, unilateral, side‐locked headache attacks, lasting about 15 minutes, and associated with ipsilateral tearing. Headaches were triggered by cough, sneezing, laughing, or bending forward. Both patients experienced a marked and sustained improvement with indomethacin, and both relapsed when it was interrupted. Conclusions: These cases suggest the existence of transitional phenotypes, or shared pathogenic mechanisms, between CH and CPH, two indomethacin‐responsive headaches. A more comprehensive analysis of different CH subtypes is necessary to understand their relation with other primary headaches.